Carotenoids as Bioreporter for Environmental Toxicants Assessment - Wong, Ling Shing; Ong, Ghim Hock; Cheng, Wan Hee (2016)
Environmental pollution is a global crisis due to the anthropogenic activities. Conventional chemical analytical tools and biosensors are effective tools in environmental toxicant assessment. For whole cell biosensors, chlorophyll was a well-studied pigment as bioreporter for the presence of environmental toxicants, but other pigments were not widely reported. In this paper, the usage of another widespread photosynthetic pigments- carotenoids as bioreporter of environmental toxicant is discussed through a few possible biosensor designs, with the sensitivity, reproducibility and storability evaluated. The carotenoids are found to be good candidate as bioreporters as the pigments response was acceptable with dosage dependency. However, the storability was still an issue which a better immobilization or storage condition was the key to a better results.